Analisis Pengaruh Model Pembelajaran Course Review Horay (CRH) Terhadap Hasil Belajar Siswa Sekolah Dasar - Ujang Jamaludin; Sigit Setiawan; Siti Halilah Sufinah; Yuni Eggriani; Zeta Hazara (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Course Review Horay Learning Model is a model that helps the learning process become more conducive and active. This study aims to analyze the effect of the Course Review Horay (CHR) learning model on student learning outcomes in elementary schools. The method in this study uses qualitative research with data collection techniques, namely literature studies. The subject in this writing refers to 6 relevant journals. The results of this study indicate that the Course Review Horay (CRH) learning model has an influence on student learning outcomes.